(untitled) (International Journal of Environmental Sciences, 2025)
The art of fabricating false-truths and disrupting reality to achieve personal success and prosperity has led to the exploitation and threatening of the survival of humankind in this post-truth era. Such a hunt to reach the epitome of self-esteem and self-promotion can knowingly or unknowingly expose the darker shade of the personality in a human. Considering this demoralized condition of our society, the present research article engages in close-reading and analysis of the central character Mukundan Unni in the Malayalam movie Mukundan Unni Associates (2022), directed by Abhinav Sundar Nayak, with an aim to track down how Mukundan Unni’s character depicts the extreme level of the characteristics of the ‘dark tetrad personality’ and its impact over a post-truth epoch. This study on the horrendous impact of the dark tetrad personality portrayed in the life of the protagonist, Adv. Mukundan Unni, explores the extent of vulnerability to which deceiving others has turned out to be a very natural human instinct. The article explains how the character becomes relevant in today’s post-truth era by proving its intentional role in warning its readers against the dystopian representations of a post-truth world. Analysing Mukundan Unni Associates through the theoretical framework of dark tetrad personality and the post-truth condition serves as a realm to break the existing normalized norms of morality and alerts the reader of the deceiving nature of the society.